Oral Ritual Traditions and Local Islamic Cultural Identity on the Riverbanks of Kuala Kapuas City - Arbainsyah Arbainsyah; Hamdanah Hamdanah; Mazrur Mazrur (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Oral tradition plays a crucial role in maintaining the cultural identity, religious values, and social norms of the Muslim community in the riverbanks of Kota Kapuas, Central Kalimantan. This tradition encompasses ritual processes such as the provision of water containers and traditional utensils, which are passed down through generations through collective memory and verbal practices. This research is a field research study, employing ethnographic and hermeneutic approaches, involving direct observation, in-depth interviews, and visual documentation as analytical materials with four traditional practitioners and religious figures/traditional elders as informants. Data were analyzed through symbolic and contextual interpretation, with source triangulation to ensure validity. The findings indicate that oral tradition serves as a means of transmitting values, norms, and collective identity, as well as a space for cultural negotiation within the framework of the acculturation of Islam and local culture. This tradition also serves as an important source of oral history because many customary practices are not recorded in written manuscripts, but are instead passed down orally through the community's collective memory. Thus, oral ritual tradition not only preserves cultural richness but also enriches insight into the dynamics of changing social and religious identities in the riverbanks of Kota Kuala Kapuas.